“THE SCHOOL OF LESSONS” MODEL OF PARENTAL COMPENSATION IN STRENGTHENING FAMILY RELATIONSHIPS (Eureka Journal of Humanities and Social Research, 2026)
This article analyzes the importance of the principle of mutual compromise between parents in strengthening family relations based on the “model school” model. It scientifically highlights the influence of parents on the upbringing of children through their personal example, the formation of moral values, and their role in creating a healthy social environment, and develops practical recommendations. It also shows the impact of a positive environment in the family on sustainable development.
Keywords: Family relations, compromise, parents, model, upbringing, morality, values, social environment, child, stability.